The Theory and Praxis of Workers Cooperatives as Models of the Social Economy and Paradigm for Capital Innovation - San Gabriel, Hilda; Bungato , Guillermo (Social Sciences and Development Review, 2017)
Anchored on presenting the theory and praxis of workers cooperatives as models of the social economy, the researchers believe that cooperative enterprises, the most humanist type of organization to thrive in the last two centuries, were able to change poor people’s and marginalized worker’s lives by providing employment opportunities, thus uplifting their socioeconomic condition. The hypothesis is that a firm competing within the mainstream, local, and/or global markets can survive not only because of the profit orientation of the business enterprise but more due to its social characteristics and value for the member worker-owner of the cooperative firm, which is contrary to the dominant business model exposed by Friedman, whose major concern is the profit bottom line. It is also asserted that the organizational coherence and adherence to the universally accepted cooperative principles are some of the reasons why these cooperative business organizations exist.
Keywords: social economy; workers co-op; social enterprises; theory and praxis; capital innovation